Influence of Organic and Inorganic Fertilizers on the Growth, Leaf Yield, Chlorophyll and Protein Contents of Stevia Grown in Different Soil Types - Khanom, S; Saha, BK; Islam, MT; Chowdhury, MAH (Progressive Agriculture, 2013)
A pot experiment was conducted in the open net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh from January to June, 2007, to study the effect of organic and inorganic fertilizers on the growth, leaf yield, chlorophyll and protein contents of Stevia rebaudiana (Bert.). The experiment was laid out in completely randomized design with three replications having 16 treatment combinations. Four types of soil viz., saline, acidic, calcareous and non-calcareous soils were collected from Khulna, Tangail, Natore and Mymensingh districts of Bangladesh, respectively. Two organic (poultry manure and cow dung) and one inorganic fertilizers @ the recommended dose along with a control were used as treatment factor. The experimental results indicated that different soil types significantly influenced all parameters studied. The highest values of all parameters were obtained from the plant grown in noncalcareous soil which was identical with acidic soil for some parameters. Different types of organic and inorganic fertilizer had also significant influence on all plant parameters. In all cases, the highest values were recorded from the plant fertilized with chemical fertilizers. Poultry manure and cow dung also showed identical results with chemical fertilizer in most cases. Interaction effect of different types of soil and fertilizer showed significant variation for most of the parameters studied except chlorophyll and protein contents. Plants grown in noncalcareous soil fertilized with chemical fertilizers exhibited the best performance in most of the cases. The overall results suggested that stevia can be cultivated in noncalcareous and acidic soils fertilized with chemical fertilizers along with poultry manure favoring the productivity of stevia. DOI: http://dx.doi.org/10.3329/pa.v19i1.16986 Progress. Agric. 19(1): 23 - 31, 2008